2013
DOI: 10.1016/j.mri.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Early assessment of breast cancer response to neoadjuvant chemotherapy by semi-quantitative analysis of high-temporal resolution DCE-MRI: Preliminary results

Abstract: Purpose To evaluate whether semi-quantitative analysis of high temporal resolution dynamic contrast-enhanced MRI (DCE-MRI) acquired early in treatment can predict the response of locally advanced breast cancer (LABC) to neoadjuvant chemotherapy (NAC). Materials and Methods As part of an IRB-approved prospective study, 21 patients with LABC provided informed consent and underwent high temporal resolution 3 T DCE-MRI before and after 1 cycle of NAC. Using measurements performed by two radiologists, the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 40 publications
1
41
1
Order By: Relevance
“…Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) is a common method for evaluating tumor response to therapy in a variety of cancers (13), including breast (4, 5). DCE-MRI acquires images before, during, and after injection of a contrast agent to characterize, for example, tumor-related perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) is a common method for evaluating tumor response to therapy in a variety of cancers (13), including breast (4, 5). DCE-MRI acquires images before, during, and after injection of a contrast agent to characterize, for example, tumor-related perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Studies focused on MRI imaging parameter changes after cycle 1 demonstrated AUCs greater than 0.70 when predicting final pCR (22, 23). DCE-MRI kinetic parameters after 2 cycles of anthracycline-based NAC were also shown to be predictive of final clinical and pathologic response after 6 cycles (24).…”
Section: Discussionmentioning
confidence: 99%
“…DCE-MRI kinetic parameters after 2 cycles of anthracycline-based NAC were also shown to be predictive of final clinical and pathologic response after 6 cycles (24). Interestingly, many of these studies also showed that change in MRI-derived tumor size did not predict pathologic response (22, 24). Analysis of 216 patients from the prospective ACRIN 6657/I-SPY TRIAL showed that the AUCs for predicting pCR after one cycle of anthracyline-based chemotherapy using MRI was 0.64 for longest diameter (LD) measurement, 0.70 for volume measurement and 0.57 for signal enhancement ratio (SER) measurement (25).…”
Section: Discussionmentioning
confidence: 99%
“…Because of these advantages, DCE-MRI is considered as a promising imaging technique for tumor staging (Delongchamps et al , 2011) and treatment planning (van der Heide et al , 2012). In the area of treatment response assessment, DCE-MRI is also capable of monitoring the therapeutic effect of radiotherapy (Cabrera et al , 2013; Wang et al , 2015), chemotherapy (Abramson et al , 2013; Yankeelov et al , 2007) and anti-vascular drugs (O’Connor et al , 2012). …”
Section: Introductionmentioning
confidence: 99%